International Code of Conduct on the distribution and use of pesticides (Amended to include prior informed consent in Article 9 as adopted by the 25th Session of the FAO Conference in November 1989) (FAO RomeIT, 1990)
Sets forth responsibilities and establishes voluntary standards of conduct for all public and private entities engaged in or affecting the distribution and use of pesticides.
DC